Pro-Environmental Behavior among Urban Millennial Workers: a Focus Group Discussions - Marbun, Yovita Ramos; Artiawati; Azaria, Renny (Journal of Educational, Health and Community Psychology, 2025)
Waste management has been a critical issue in Indonesia, demanding urgent attention for sustainability and public health. The lack of public awareness underscored the need to understand pro-environmental behaviors, particularly waste sorting. Indonesia’s urban millennial workforce was expected to drive change in raising environmental awareness. This study explored the waste sorting behavior of urban millennial workers, influenced by work and family environments. Using Focus Group Discussions (FGDs) with 18 participants (8 in Jakarta, 10 in Surabaya), data was analyzed using NVIVO 14. The qualitative approach was chosen for its ability to provide in-depth insights into participants’ behaviors and perspectives. Findings revealed that inadequate facilities, lack of social support, and weak regulation enforcement hindered waste sorting, despite positive attitudes toward sustainability. The study suggested improving infrastructure, enforcing regulations, and enhancing socialization to promote sustainable waste sorting among urban millennial workers. The findings emphasized the need for policy development and corporate responsibility and recommended further research on the long-term effects of education, socialization, and regulation enforcement.